2018
DOI: 10.25115/psye.v10i3.2135
|View full text |Cite
|
Sign up to set email alerts
|

Drunkorexia: empirical investigation and analysis of the characteristics of the phenomenon in an Italian sample of adolescents and young adults

Abstract: Introduction: the term drunkorexia refers to the act of self-imposed utilization of extreme weight control methods to compensate for alcohol consumption typically observed among university students. Despite its diffusion, there is a lack of research investigating the presence of this new alarming trend in Italy. Aim: this study estimates the frequency of drunkorexia behaviours in a sample of Italian youth aged 14-24, explores the motivations for alcohol consumption among those presenting drunkorexia-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…All data analyses were conducted using SPSS Statistics Version 25.0. Preliminary, consistent with prior research [ 36 , 63 ], gender differences were investigated by conducting a series of one-way analyses of variance (ANOVAs) on the study variables: FAD, alcohol consumption, compensatory behaviors (fasting, vomiting and use of laxatives), living arrangement (living alone and living with family), social support, eating and weight concerns, and BMI self-reported. We carried out a multivariate analysis of variance (MANOVA) on Emotion Regulation dimensions.…”
Section: Methodsmentioning
confidence: 99%
“…All data analyses were conducted using SPSS Statistics Version 25.0. Preliminary, consistent with prior research [ 36 , 63 ], gender differences were investigated by conducting a series of one-way analyses of variance (ANOVAs) on the study variables: FAD, alcohol consumption, compensatory behaviors (fasting, vomiting and use of laxatives), living arrangement (living alone and living with family), social support, eating and weight concerns, and BMI self-reported. We carried out a multivariate analysis of variance (MANOVA) on Emotion Regulation dimensions.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, previous research has highlighted the association between eating disorder patterns and drunkorexia. For instance, an Italian study revealed that young female adults diagnosed with eating disorders were more subject to indulge in Drunkorexia behaviors [ 25 ]. Furthermore, earlier research on eating disorders suggest that individuals with several types of eating disorders are characterized by emotional regulation difficulties in addition to interoceptive deficits [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…El patrón habitual de la drunkorexia incluye contar las calorías de los alimentos y bebidas que ingerirán, dejar de comer por horas o días enteros previo a la ingestión de las bebidas alcohólicas y, después, incrementar la actividad física para quemar las calorías consumidas en exceso (Martínez, López-Espinoza, Navarro Meza, López-Uriarte y Salazar Estrada, 2014). Parece más común entre las mujeres universitarias entre 18 y 24 años con distorsión de la imagen corporal (Pietrabissa et al, 2018). La drunkorexia puede presentar consecuencias físicas y psicológicas graves (Villarino, 2012).…”
Section: Alcoholunclassified